Organizational Culture and Employee Transfers Influence on Employee Performance with Work Motivation as Moderator Variable - Kunto Wibisono; Siti Kusandhitasari Jayaningrum; Yuyun Wahyuni; Carmelita Amaya Dacruz (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to examine the influence of the variables Organizational Culture and Employee Transfers on Employee Performance with Work Motivation as a moderator variable at PT Angkasa Pura I (Persero). The case study was conducted on employees of PT. Angkasa Pura I (Persero) at El Tari Kupang Airport by distributing questionnaires directly. The sample for this research consisted of 200 respondents. The analysis method used is a multilevel test (Hierarchical regression) using the statistic program for social science version 24. Based on the results of data analysis, it shows that H1: Organizational Culture is proven to have a significant influence on Employee Performance, H2: Employee Transfers are proven to have a significant influence on Employee Performance, H3: Organizational Culture is proven to have a significant influence on Employee Performance with Work Motivation as a moderator variable, and H4: Mutations Employees are proven to have a significant influence on employee performance with work motivation as a moderator variable at PT Angkasa Pura I (Persero). Keywords: organizational culture, employee transfers, employee performance, work motivation